A division method for shallow tunnels and deep tunnels considering soil stress path dependency. (July 2021) - Zhang, Pei; Lu, Dechun; Du, Xiuli; Qi, Jilin
Abstract: Critical burial depth plays an important role in tunnel design and analysis. So, the division method for deep tunnels and shallow tunnels is perceived as a main concern. Considering the soil stress path dependency, this paper investigates the construction mechanical behavior of soil mass at different burial depths, and aims to explore a method for identifying critical burial depth. Firstly, using the Eulerian method and stress return mapping scheme, an elastoplastic algorithm applicable to double loading criteria was developed for a soil constitutive model considering complex stress paths. Then, the developed algorithm was implemented into a user-defined material subroutine (UMAT) and validated through numerical triaxial tests under different stress paths. Subsequently, the UMAT was used to model tunnel excavation in soils. The simulated results were compared with the results that from practical engineering, which shows that the UMAT could accurately predict the ground surface settlement. On the basis of this, the stress distribution and deformation performance in soil during tunneling at different burial depths were explored. Finally, the division method for differentiating shallow tunnels and deep tunnels in soil was discussed and a method for determining the critical depth was proposed.